Effect of packing characteristics on the discrete element simulation of elasticity and buckling. (May 2016) - Kumar, Rishi; Rommel, Sarshad; Jauffrès, David; Lhuissier, Pierre; Martin, Christophe L.
Abstract: Discrete Element Method (DEM) simulations are used to model the elastic properties of a continuous material. The preparation route of the particle packing is shown to have a significant effect on the macroscopic properties. We propose simple relations, generalized from the mean field solution, that are able to fit DEM results. These relations introduce only basic microstructural features such as the coordination number and the packing density. When the tangential to normal stiffness ratio increases above unity, the material becomes potentially auxetic. Buckling is also explored with DEM, and results on cylindrical bars are compared to the classic Euler results for critical stress. Abstract : Highlights: Preparation route affects the elastic response of packings of bonded particles. Simple equations are proposed for the elastic response. These equations introduce simple packing characteristics: coordination, density. Auxetic materials may be modelled with bonded particles. Quasi-static buckling of cylindrical bars is treated with the model.